An Applied Study of Tax Management as A Strategic Tool for Cost Minimization in the Business Sector - Siringoringo, Magdalena Judika Br.; Simanjuntak, Sri Ida Royani (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
Basically, taxes are an important source of revenue that will be used to finance state expenditures, both routine and development expenditures. Conversely, for companies, taxes are a burden that will reduce the company's net profit. In order for this burden to be minimized, it is necessary to implement effective tax management through tax planning. This study aims to determine and study the application of corporate income tax planning in business sector businesses by using the company's income statement which is used to make fiscal corrections, so that it will produce fiscal financial statements and fiscal income which will be used to compile tax planning and will be compared to profit before planning and profit after tax planning. The results showed that before the implementation of tax planning, the tax to be paid was Rp 132,851,711 while after planning, the tax to be paid was Rp 126,321,378 in 2011. By doing good and proper tax planning, the business sector can optimize the tax to be paid so that it can be used to finance other expenses.